'A more public arena': Jeff Koons' Reinvention in the Midst of Reaganism. Issue 3 (21st January 2020) - Perl, AnnMarie
Abstract : Critics have argued since 1986 that Jeff Koons lacks criticality and, moreover, cynically capitalizes on art's commodification. This essay provides a focused historical account of Koons' development during the late 1980s, demonstrating how he reinvented his artistic project following these critiques, in part by adopting a farcical utopian social and political agenda, in which all people would become aristocrats. Koons was not a political activist and never imagined that this agenda could come to pass. Rather, his resulting artwork, which was rich in political references, allusions and associations, revealed how people had been persuaded by a version of this fantastic promise at their expense. Koons provocatively personified and pictured the way that politics was then remaking American society. In particular, his Banality series of 1988–89 produced a jarring picture puzzle that positioned viewers between the extremes of identification with, or differentiation from, either the disenfranchised or the elite.